Essence of, Approaches to and Transformation Process in Higher Education for Sustainable Development: A Critical Review - Sobhani, Farid A; Amran, Azlan (IIUC Studies, 2015)
The study aims at reviewing the essence of sustainable education, highlighting its different approaches and analyzing transformation process of higher education for sustainable development (HESD). Since there is lack of sustainability research in the developing countries, the study addresses the issues of higher education towards sustainability from the perspective of a developing nation. This research is qualitative and descriptive in nature. It considered extensive literature survey to meet the research objectives. The study found that the issue of higher education for sustainable development got global attention especially in the Western society. In Mexico, many public universities introduced sustainability education as core course at the graduate and post-graduate level. Among the Asian nations, Malaysia has set an example taking initiative to transform higher education for a sustainable society. Universiti Sains Mlaysia (USM) got APEX status incorporating that dimension in the program. Bangladesh, the local context of the study, is lagging far behind in attempting to sustainable education. Both public and private universities are facing many challenges towards that dimension, which are highlighted in this study. IIUC Studies Vol.9 December 2012: 113-136